Open Reduction and Internal Fixation of Extraarticular Scapular Neck and Body Fractures With Good Short Term Functional Outcome - Mohd Asihin, Muhammad Azrin; Bajuri, Mohd Yazid; Ganaisan, Premganesh K.; Ahmad, Abdul Rauf (Frontiers in Surgery, 2019)
Background: The study aims to evaluate the short-term functional outcome of open reduction and internal fixation of extraarticular scapular neck and body fractures treated at our centre over a period of two-year duration at a tertiary referral centre. Patients and Methods: Between October 2015 to October 2017, we operated on 20 extraarticular scapular neck and body fracture. Ten were available for a one-off assessment. The mean time to surgery was 10 days (range, 3-19 days) and one-off assessment was done within 6-24 months (mean, 13 months). Indications includes (1) medial/lateral displacement (M/L) > 20 mm, (2) M/L > 15 mm if angular deformity > 300, (3) Angular deformity > 450, (4) Double lesion of superior shoulder suspensory complex (SSSC), with displacement > 10 mm in both lesion, (5) Glenopolar angle (GPA) < 220, and (6) open scapular fracture. The functional outcome was measured using range motion and strength. Patient-reported outcome was assessed using Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire and Short-Form-36 (SF-36) version 1. Results: All patients achieved radiological union at time of assessment. None of the patients had postoperative complications. The mean DASH score was 19.3 (range, 1.7 – 39.3). All subcategories of SF-36 questionnaire scores between 70 to 89.6, with exception to REE (role limitations due to emotional problems) and REP (role limitations due to physical health). The average range of motion for the injured shoulders; forward flexion 1570, abduction 1140, and external rotation 420. The strength of operated and non-operated shoulders, respectively, 6.5 and 8.1 kgF of forward flexion, 5.5 and 7.2 kgF of abduction, and 4.1 and 6.3 kgF of external rotation. Conclusion: Open reduction and internal fixation of surgically indicated scapular neck and body fracture is feasible with predictably good functional outcome. The reduced external rotation ROM and strength may be due to the use of Classic Judet approach, however we do not enough data to support this.